Climatically stable landscapes predict patterns of genetic structure and admixture in the Californian canyon live oak. (25th September 2014) - Ortego, Joaquín; Gugger, Paul F.; Sork, Victoria L.; Riddle, Brett
Abstract Aim We studied which factors shape contemporary patterns of genetic structure, diversity and admixture in the canyon live oak (Quercus chrysolepis). Specifically, we tested two alternative hypotheses: (1) that areas with high habitat suitability and stability since the Last Glacial Maximum (LGM) sustain higher effective population sizes, resulting in increased levels of genetic diversity; and (2) that populations from areas with lower habitat stability show higher levels of genetic admixture due to their recurrent colonization by individuals originating from genetically differentiated populations. Furthermore, we analysed the relative importance of past and current habitat suitability and their additive effects on contemporary patterns of genetic structure. Location California, USA. Methods We sampled 160 individuals from 33 localities across the distribution range of the canyon live oak in California and then combined information from 13 nuclear microsatellite DNA markers and climate niche modelling to study patterns of genetic variation in this species. We used Bayesian clustering analyses to analyse geographical patterns of genetic structure and admixture, and circuit theory to generate isolation‐by‐resistance (IBR) distance matrices. Results We found that the degree of genetic admixture was higher in localities with lower inferred population stability, but that genetic diversity was not associated with habitat suitability or stability. Landscape genetic analyses identified habitat stability as the primary driver of population genetic differentiation. Main conclusions This study shows that habitat stability can be a major factor shaping genetic variation in wind‐pollinated trees and supports the idea that stable regions contribute to genetic connectivity across different climatic periods. To our knowledge, this study is the first to report an association between patterns of genetic admixture and stability of local habitat.